MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI MEDIA BUSY BOOK DI POS PAUD MAWAR 2 - Lisnawati, Lisnawati; Supriatna, Asep; Kurniasih, Kurniasih (Penerbit Lafadz Jaya, 2025)
Fine motor skills refer to the coordinated movements of small muscles, particularly in the fingers and wrists, requiring precise eye–hand coordination. Based on Initial observations conducted in April 2025 at POS PAUD Mawar 2 revealed that many children aged 5-6 had difficulty, in Kamojing Village, it was found that many children aged 5-6 had difficulty performing activities that required fine motor skills, performing activities that require fine motor skills. Mastery of these skills supports children’s creativity and independence in daily activities. One effective medium to develop fine motor abilities is the busy book, which provides hands-on, interactive learning experiences. This study aimed to examine the improvement of fine motor skills using busy books among 5–6-year-old children in Class B at POS PAUD Mawar 2 Kamojing. The research involved 14 participants and employed a Classroom Action Research (CAR) design implemented over two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through structured observation, documentation, and interviews. The findings revealed substantial progress in children’s fine motor development. Initially, no children were classified as Very Well Developed (BSB) or Well Developed as Expected (BSH), with 28.57% in the Developing (MB) category and 71.43% in Not Yet Developed (BB). By the end of Cycle I, the distribution shifted to 14.29% BSB, 28.57% BSH, and 57.14% MB. In Cycle II, 85.71% of children achieved BSB and 14.29% BSH, with no children remaining in the MB or BB categories. Notable improvements were observed in buttoning clothes, opening, and closing bottle caps, and precisely pinching pompoms. These results demonstrate that the busy book is an effective and engaging tool for enhancing fine motor skills in early childhood education settings.